Evaluasi Sistem Budidaya Tanaman Asystasia gangetica T. Anderson yang Ditanam dengan Jarak Berbeda di Bawah Naungan Kelapa Sawit (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
The objective of this experiment was to evaluate the cultivation, production and quality systems of Asystasia gangetica T. Anderson as forage in palm oil plantations. This research was arranged in a factorial randomized block design with 2 factors, i.e. palm plantation ages (6 and 8 years old) and different plant spacing (10x10 cm, 25x25 cm, and 40x40 cm). Variables observed were plant height, number of leaves, number of primary and secondary branches, leaf length and width, biomass production, and nutrient contents. Spacing was significantly affected (p